1969
DOI: 10.1021/ja01038a041
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the osmium tetroxide-catalyzed oxidation of acetone and ethyl methyl ketone by alkaline hexacyanoferrate(III) ion

Abstract: produced during the ozonolysis of unsymmetrical olefins, did not interfere with the measurements. It was found that the cis/trans distributions did not depend on the extent of the reaction. The given proportions (Tables V and VI) were calculated from five to seven independent experiments in each case and they are expressed with a 95 % confidence limit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…28,29 There are a number of papers on the kinetics of a variety of organic oxidation reactions with this anion as a catalyst in the presence of a number of co-oxidants. [30][31][32][33] (i ) Oxidation of alcohols, aldehydes, alkyl halides and benzylamines. Solutions of cis-[OsO 4 (OH) 2 ] 2Ϫ were made from OsO 4 and molar aqueous NaOH or KOH.…”
Section: (C) Osomentioning
confidence: 99%
“…28,29 There are a number of papers on the kinetics of a variety of organic oxidation reactions with this anion as a catalyst in the presence of a number of co-oxidants. [30][31][32][33] (i ) Oxidation of alcohols, aldehydes, alkyl halides and benzylamines. Solutions of cis-[OsO 4 (OH) 2 ] 2Ϫ were made from OsO 4 and molar aqueous NaOH or KOH.…”
Section: (C) Osomentioning
confidence: 99%
“…Homogeneous catalysis by ruthenium and osmium compounds has been reported by several workers but the use of iridium(III) chloride as a homogeneous catalyst in acidic medium has not yet been reported. In the present study it was observed that the average concentration of iridium(III) chloride required to catalyze the oxidation of cycloketones lies in the 10 À6 M range, while at least 10 times higher concentrations of ruthenium(III) chloride with cerium(IV) sulphate in acidic medium [5] and osmium(VIII) oxide with hexacyanoferrate(III) in alkaline medium [6] were required to oxidize various ketones. Herein we report a study of the oxidation of cyclopentanone and 2-methyl cyclohexanone by cerium-(IV) sulphate in aqueous sulphuric acid medium catalyzed by iridium(III) chloride at constant ionic strength of the medium.…”
Section: Introductionmentioning
confidence: 53%
“…The hexacyanoferrate(III)-hexacyanoferrate(II) system, which has higher redox potential than Cu(II)-Cu(I), substantiates a better possibility for the rapid oxidation of the free radical with hexacyanoferrate(III) in the alkaline medium and the rapid oxidation of the free radicals might completely mask the polymerization. Sometimes the vinyl compounds themselves are oxidized under the experimental conditions used and the test for free radicals fails [32]. In view of less than unit order in [OH -] and also high alkali concentration, the active species of osmium(VIII) is considered as [OsO 5 (OH)] 3- [33], which is shown in prior equilibrium of Scheme 1.…”
Section: Discussionmentioning
confidence: 99%